Effect of Daily Oral Lactobacillus plantarum PS128 on Exercise Capacity Recovery after a Half-Marathon - Szu-Kai Fu (MDPI AG, 2021)
A half-marathon (HM) is a vigorous high-intensity exercise, which could induce lower extremity musculoskeletal injury risks for recreational runners. They usually consume nonsteroidal anti-inflammatory drugs (NSAIDs) in order to shorten their return to play but ignore the side effects, such as peptic ulcers and renal and vascular disorders. Lactobacillus plantarum PS128 (PS128) could improve inflammation and oxidative stress by modulating the gut microbiota, thus potentially improving muscle damage and recovery. However, few studies have addressed the PS128 exercise capacity recovery 96 h after HM. Thus, this study aimed to investigate the effect of PS128 on exercise capacity and physiological adaptation after HM. A double-blind, randomized, placebo-controlled, counterbalanced, crossover trial was used for the experiment. HM was conducted at the beginning and end of the 4-week nutritional supplement administration. Eight recreational runners took two capsules (3 × 1010 CFU/capsule) of PS128 each morning and evening before meals for 4 weeks as the PS128 treatment (LT), or they took two capsules of placebo for 4 weeks as the placebo treatment (PT). In both treatments, an exercise capacity test (lower extremity muscle strength, anaerobic power, lower extremity explosive force, and aerobic capacity) and blood test (muscle fatigue, muscle damage, oxidative stress, and renal injury) were performed before the administration of the nutritional supplement (baseline), 48 h before HM (pre), and 0 h (0 h post), 3 h (3 h post), 24 h (24 h post), 48 h (48 h post), 72 h (72 h post), and 96 h (96 h post) after HM. There was no significant difference in the total duration of HM between PT and LT, but PT was found to be significantly higher than LT at Stage 4 (15,751–21,000 m) of HM (3394 ± 727 s vs. 2778 ± 551 s, p = 0.02). The lower extremity muscle strength measured using an isokinetic dynamometer in PT was significantly lower than that in LT at 72 h after HM. The lower extremity explosive force from the countermovement jump (CMJ) in PT was significantly decreased compared to 24 h prior. There was no significant difference between anaerobic power and aerobic capacity between the two treatments after HM. After HM, LT had lower muscle damage indices, such as myoglobin (3 h post-PT vs. -LT: 190.6 ± 118 ng/mL vs. 91.7 ± 68.6 ng/mL, p < 0.0001) and creatine phosphokinase (24 h post-PT vs. -LT: 875.8 ± 572.3 IU/L vs. 401 ± 295.7 IU/L, p < 0.0001). Blood urea nitrogen recovered in 24 h (24 h pre- vs. post-LT, p > 0.05) and higher superoxide dismutase was found in LT (96 h post-PT vs. -LT: 0.267 ± 0.088 U/mL vs. 0.462 ± 0.122 U/mL, p < 0.0001). In conclusion, PS128 supplementation was associated with an improvement in muscle damage, renal damage, and oxidative stress caused by HM through microbiota modulation and related metabolites but not in exercise capacity.